Synbiotic loaded chitosan-Ca-alginate microparticles reduces inflammation in the TNBS model of rat colitis - Tanja Petreska Ivanovska; Kristina Mladenovska; Zoran Zhivikj; Maja Jurhar Pavlova; Ivica Gjurovski; Trpe Ristoski; Lidija Petrushevska-Tozia (Elsevier, 2017)
New therapeutic strategies against inflammatory bowel disease (IBD) consider the usage of probiotics, prebiotics and synbiotics as beneficial for the intestinal microbial balance. Limitations of such an approach are addressed into difference in survival, persistence, colonization and variable effects among different probiotic strains, lack in understanding of probiotic mechanisms of action, as well the complex etiology of IBD. The anti-inflammatory activity of Lactobacillus casei 01 (L. casei 01) was assessed in trinitrobenzenesulphonic (TNBS) acid model of rat colitis when the probiotic was used alone and/or in combination with oligofructose-enriched inulin (Synergy 1), and as synbiotic (L. casei 01 + Synergy 1) loaded chitosan-Ca-alginate microparticles; all suspended in ayran. The results from the probiotic/ synbiotic treatments (8.5–8.9 log CFU g 1 L. casei 01 and 1.5% Synergy 1) have shown reduction in the colonic damage and increased lactobacilli counts in feces. Lactobacilli translocation to sterile extra- intestinal organs demonstrated acceptable safety of the probiotic strain used. The best effect at reducing inflammation and lesions associated with a significant decline in myeloperoxidase (MPO) activity was observed in rats that received synbiotic microparticles. This finding suggests colon targeted delivery of the probiotics/synbiotics, as an advantageous approach in prevention and treatment of IBD.
Keywords: Lactobacillus casei 01; Oligofructose-enriched inulin; Trinitrobenzenesulphonic acid; Rat colitis; Chitosan-Ca-alginate microparticles